The Removal Of Heavy Metals By Phytoremediation Using Cyperus Alternifolius - Rahim, Noor Hafizah Ab (Universiti Sains Malaysia, 2017)
The ability of Cyperus alternifolius was studied in the removal of heavy metals. Three sets of heavy metals removal experiment were set up (1, 2 and 3), where each set contain containing tap water, heavy metals solution and iron sulfate solution. This research, experimental set-up 1, 2 and 3 showed a drop in pH throughout the treatment process. Elemental analysis of Cu, Mn, Ni and Fe ions were determined by AAS. At the end of the phytoremediation, concentration of metals in set-up 1, 2 and 3 were lesser compared to their initial metal concentration indicating the efficiency of Cyperus alternifolius in the removal of heavy metal. In set-up 1, Mn > Cu = Fe > Ni by percent of 89 > 84 > 80. Set-up 2, within the range of Cu > Fe > Mn > Ni within the percent of 90 > 83 > 81 > 72. Element accumulated at the roots, stems and leaves were analyzed to obtained accumulation factor (A) and translocation factor (TF). It was found that the accumulation factor of copper was highest in the experimental set up 2 in the stems by 66%. For iron, manganese and nickel the accumulation factor was highest in roots in the set-up 1 by 43%, 34% and 50% respectively. Both copper and nickel showed the highest translocation factor value of 5.66 at the stems for set-up 1 and 0.36 respectively for set up 2. Translocation factor of iron and manganese in the leaves gave values of 0.62 and 0.91 respectively. Overall, the translocation factor in set-up 1, 2 and 3 can be summarized as follow: Cu > Mn > Fe > Ni (1.34 > 0.77 > 0.45 > 0.2), Mn > Fe > Ni > Cu (0.91 > 0.62 > 0.22 > 0.01) and value of 0.17 respectively. Therefore, from the results obtained it can be concluded that Cyperus alternifolius is a hyperaccumulator that able to remove metals ions from its environments.